The Supervision of Grant Fund Management In Regional Elections For Anti-Corruption in The Election Supervisory Board (Bawaslu) of Depok City, West Java - Arya Mega Natalady Sumbayak; Wirman Syafri; Dadang Suwanda; Mansyur Achmad (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The supervision of grant fund management in regional elections is a critical component in ensuring the integrity of democracy and public accountability. This study analyzes the effectiveness of grant fund supervision in the Election Supervisory Board (Bawaslu) of Depok City from an anti-corruption perspective. Using a qualitative approach through document review, in-depth interviews, and focus group discussions, the analysis applies Tthe 12 Components of a Functional Monitoring and Evaluation System framework by Kusek (2004). The findings indicate that the supervision mechanism remains primarily administrative and output-oriented, with weaknesses in organizational structure, the absence of an internal audit apparatus, and limited human and financial resources. Nevertheless, supporting factors include staff commitment and openness to evaluation and feedback. The study concludes that strengthening a results-based supervision system requires enhancing human resource capacity, integrating supervision outcomes into policy formulation, and establishing inter-agency coordination mechanisms to prevent misuse of grant funds.